Reading Israel, reading America : the politics of translation between Jews - Asher, ʻOmri (Stanford studies in Jewish history and culture., 2020)
Reading Across Borders analyzes the relationship between Jewish Americans and Jewish Israelis through the lens of translation studies, shedding light on the different ways in which each Jewish cultural center responded to the challenge--and potential inspiration--represented by the other.